Imaginaries, directionalities, agency and new path creation - Anna Herzog (Review of Regional Research, 2022)
This study focuses on how imaginaries and directionalities, i.e. the interpretation of the urban economic history and the derived fundamental perceptions, conventions, mental representations and identities, influence stakeholder behaviour (agency) with regard to enabling or inhibiting new path creation. Applying concepts of evolutionary economic geography (EEG) and sociology, this paper aims to contribute to the literature on the impact of historical dependences on urban structural change processes. These theoretical reflections are applied to an empirical case study analysing the decline and renaissance of the textile industry in Mönchengladbach, Germany. The qualitative case study is based on a~document-based analysis and seven guideline-based interviews with local experts from the textile and clothing industry. It concludes that imaginaries and directionalities can take effect via four mechanisms: communication and cooperation, motivation, training and employment, and research and innovation.
Keywords: 910; New path creation; Agency; History; Mönchengladbach; Evolutionary economic geography